2018
DOI: 10.1155/2018/4545623
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic Steroid Use for Weight and Strength Gain in Critically Ill Patients: A Case Series and Review of the Literature

Abstract: Background An important long-term complication of critical illness is significant weakness and its resulting functional impairment. Recent advances have aimed to prevent critical illness weakness via early mobilisation of patients, minimising sedation, and optimising nutrition. One other potential treatment may be to provide anabolic support in the recovery phase, especially as patients have decreased levels of anabolic hormones. Case Presentation We describe a case series of 4 patients who had either (1) prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Combined with structured exercise, this approach has shown clinical benefit [ 37 , 38 ]. A case series describes the potential role and benefit of nandrolone (an injectable anabolic steroid) for weight gain and ICU-related myopathy for patients in the recovery phase of critical illness [ 39 ]. While the combination of an anabolic agent with early exercise and adequate nutrition in the ICU is likely the key to optimize muscle strength and functional outcomes for recovering critically ill patients [ 36 ], no large randomized controlled trials have yet led to guidelines addressing anabolic agent supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with structured exercise, this approach has shown clinical benefit [ 37 , 38 ]. A case series describes the potential role and benefit of nandrolone (an injectable anabolic steroid) for weight gain and ICU-related myopathy for patients in the recovery phase of critical illness [ 39 ]. While the combination of an anabolic agent with early exercise and adequate nutrition in the ICU is likely the key to optimize muscle strength and functional outcomes for recovering critically ill patients [ 36 ], no large randomized controlled trials have yet led to guidelines addressing anabolic agent supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of anabolic steroids in the recovery phase after critical illness patients, assist them to regain their muscle strength with the addition of early mobility programs. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…The dose selection was based on our own previous experience, as well as published data from other patient populations, and duration based on the likelihood of the patients still remaining in hospital for ongoing administration and measurements. [11][12][13] The rst dose was administered while the patient was still in the ICU, but subsequent doses could be given when the patient had gone to the ward. The study drug was only administered if the patient was still in hospital, and thus not all patients received 3 doses.…”
Section: Study Treatmentmentioning
confidence: 99%
“…[10] Testosterone and oxandrolone have been shown to have bene cial effects on muscle catabolism in patients with burns. [11] Small previous studies have suggested nandrolone to be bene cial for patients recovering from critical illness. [12,13] We designed a phase II randomised controlled trial to explore the feasibility, safety and potential bene ts on muscle strength and recovery from critical illness from nandrolone, or placebo.…”
Section: Introductionmentioning
confidence: 99%